A Short History of Transport in Japan from Ancient Times to the Present. - Black, John Andrew. (Open Book Publishers, 2022)
A Short History of Transport in Japan from Ancient Times to the Present is a unique study: the first by a Western scholar to place the long-term development of Japanese infrastructure alongside an analysis of its evolving political economy. Drawing from New Institutional Economics, Black offers an historically informed critique of contemporary planning using the example of Japan's historical institutions, their particular biases, and the power they have exerted over national and local transport, to identify how reformed institutional arrangements might develop more sustainable and equitable transport services.